COLLABORATIVE LEARNING: A STRATEGY FOR IMPROVING STUDENTS' SPEAKING SKILL - Muhammad Fikri Nugraha Kholid; Zathu Restie Utamie; Tommy Hastomo (Universitas Pamulang, 2022)
This research aimed to identify the collaborative English learning at UIN Raden Intan Lampung. Classroom Action Research is the research method in this study. The researchers employed the theory from Harmer (2007) and Dillenbourg (1999) as the fundamental theory in this research. Collaborative learning is an effective strategy for teaching Sharia Economics students at UIN Raden Intan Lampung. There are five stages in this action research: diagnosing, planning, action, observation, and reflection. The findings show that collaborative learning can improve students' speaking ability because this strategy can increase their engagement, confidence, and critical thinking to deliver their ideas in classroom activities.